Detection of paternal uniparental disomy 9 in a neonate with prenatally detected mosaicism for a small supernumerary marker chromosome 9 and a supernumerary ring chromosome 9 - Chih-Ping Chen; Ming Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Shih-Ting Lai; Shun-Ping Chang; Chien-Wen Yang; Chen-Wen Pan; Wayseen Wang (Elsevier, 2017)
Objective: We present the association of paternal uniparental disomy (UPD) 9 with mosaicism for a small supernumerary marker chromosome 9 [sSMC(9)] and a supernumerary ring chromosome 9 [r(9)]. Materials and methods: A 38-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+mar [25]/48,XY,+mar,+r(9) [4]/47,XY,+r(9) [1]/46,XY [6]. The parental karyotypes were normal. Array comparative genomic hybridization (aCGH) of cultured amniocytes revealed a result of de novo 9p13.1q21.11 (38,792,472-71,026,063) × 2.64. The marker chromosome was determined to be an sSMC(9) by spectral karyotyping and aCGH. A phenotypically normal baby was delivered at 38 weeks of gestation. During pediatric follow-ups at age two years, the neonate manifested normal psychomotor and growth development. Cytogenetic analysis, metaphase fluorescence in situ hybridization (FISH), single nucleotide polymorphism (SNP) aCGH and polymorphic DNA marker analysis were performed on the peripheral blood of the neonate. Results: The neonate's blood had the following results. Metaphase FISH confirmed coexistence of the sSMC(9) and the supernumerary r(9). The karyotype was 47,XY,+sSMC(9) [14]/48,XY, +sSMC(9),+r(9) [10]/47,XY,+r(9) [6]/46,XY [10]. SNP aCGH revealed arr 9p22.3q21.11 (14,234,165-71,035,608) × 2-3, arr 9p24.3p22.3 (216,123-14,629,321)hmz, arr 9p21.3p13.2 (24,769,722-36,732,597)hmz and arr 9q21.11q34.3 (71,013,799-141,011,581)hmz. Polymorphic DNA marker analysis showed paternal isodisomy 9. Conclusion: Individuals with mosaicism for sSMC(9) and supernumerary r(9) may be associated with paternal UPD 9.